Multiparametric mapping of neurological soft signs in healthy adults - Hirjak, Dusan; Wolf, Robert Christian; Kubera, Katharina Maria; Stieltjes, Bram; Thomann, Philipp (Brain structure & function, 2016)
Minor motor and sensory deficits or neurological soft signs (NSS) are frequently found in patients with schizophrenia at any stage of their illness. Although previous studies have reported that NSS are associated with altered structure and function within fronto-parietal areas, it remains unclear whether the neuroanatomical basis of NSS may be confounded by underlying pathological processes, and by antipsychotic treatment. Morphological brain correlates of NSS in healthy subjects have seldom been investigated. This study evaluated the relationship between NSS levels and abnormalities of subcortical and cortical structures in healthy individuals. High-resolution MRI data at 3 Tesla were obtained from 68 healthy individuals. Automated segmentation of caudate nucleus, putamen, globus pallidus, thalamus, and brainstem was performed using both FSL-FIRST and Freesurfer. The surface-based analysis via Freesurfer enabled calculation of cortical thickness, area and folding (local gyrification index). NSS were examined on the Heidelberg Scale and related to both subcortical and cortical measurements. Using two fully automated brain segmentations methods, we found no significant association between NSS levels and morphological changes in subcortical structures. Higher NSS scores were associated with morphological changes of cortical thickness, area and folding in multiple areas comprising superior frontal, middle temporal, insular and postcentral regions. Our findings demonstrate the benefit of surface-based approaches when investigating brain correlates of NSS. The data lend further support to the hypothesis that NSS in healthy individuals involve multiple cortical rather than subcortical brain regions.